The Impact of Strength Training on Bone Mineral Density and Fracture Risk in Older Adults - Azahrah, Nurul Islah; Jasman, Rika Safitri; Safitri, Salmani (ScieClouds Publishing, 2023)
With the aging population, risks associated with bone density decline, osteoporosis calls for these people to seek ways to enhance their bone health as they age. Strengthening exercise or resistance training exercise has received a lot of emphasis due to the effects on the BMD and bone health in the elderly. This literature review aims to elucidate on the effects of strength training on bone health, using its modalities of action, effectiveness and biological pathways. It has been reveled in researches that strength training causes mechanical loading on bones through exerting force on bones by osteoblasts and osteoclasts thus increasing BMD. Also, strength training enables muscles pull with a lot of force on bones, thus improving their density and strength. Changes in hormonal levels and in the indices of bone turnover – osteocalcin and C-telopeptide, all point to the fact that resistance training is beneficial in influencing bone metabolism. It forms part of the current review comparing strength training to different combinations of exercise in the prevention or treatment of bone loss or fracture in older adults, a subject on which it draws conclusions that positive outcomes include increased BMD in lumbar spine and femoral neck, decrease in fracture risk. Similarly, strength training complemented with proper nutrition and other forms of exercise increases the benefits many folds. This review shall also stress on strength training as a feasible strategy to counter age related bone densing and fracture rate and improved quality of life among the elderly.